Rapid care analysis as a Qualitative research tool to explore unpaid care work: Experience from char area in Bangladesh - Khondaker, Sahida Islam (BRAC Institute of Governance and Development (BIGD), 2022)
Every day unpaid care work is carried out all over the world and it is necessary for a society’s wellbeing. However, unpaid care work is largely ignored by economic and social public policy initiatives. Neither is it adequately valued in economic terms. In developing countries like Bangladesh, most research on unpaid care work is dominated by quantitative research methodologies that generally cannot capture how people actually experience unpaid work on a daily basis. Moreover, they neglect the arena of perceptions of unpaid work. Qualitative participatory approaches allow people to identify the extent to which unpaid work-related problems affect their communities, encourage people to assess the causes and consequences of inequitable distribution of care work and facilitate the identification of interventions from the perspectives of women and men, rather than policymakers or scholars. This paper attempts to describe and analyze the Rapid Care Analysis (RCA) as a qualitative method to study unpaid care work and establish that compared to quantitative methods, RCA as a qualitative method can capture the unequal distribution of care work in the community, measure time uses, create awareness and also find out available services, infrastructure and options to reduce and redistribute care work more comprehensively. From different RCA exercises, it is observed that both male and female participants have understood the notion of heavy and unequal care work. Through the exercise, participants recognized care work as work. Participants also came up with some solution to reduce care work. Quantitative methods cannot provide these insights. Therefore, RCA could be one of the best tools for conducting research on care work.